2021
DOI: 10.3390/pr9091675
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Processes Affect the Composition and Bioavailability of Flavones from Lamiaceae Plants: A Comprehensive Review

Abstract: Lamiaceae plants are a widespread family of herbaceous plants with around 245 plant genera and nearly 22,576 species distributed in the world. Some of the most representative and widely studied Lamiaceae plants belong to the Ocimum, Origanum, Salvia, and Thymus genera. These plants are a rich source of bioactive molecules such as terpenes, flavonoids, and phenolic acids. In this sense, there is a subgroup of flavonoids classified as flavones. Flavones have antioxidant, anti-inflammatory, anti-cancer, and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 166 publications
0
1
1
Order By: Relevance
“…The absence of antimicrobial activity of the ethanolic extract of C. citratus observed in this study is also in disagreement with several other studies that have also investigated the antibacterial effect of lemongrass [75][76][77][78]. This difference between the results of the present study and those observed in others could be explained by several factors, such as the geographical area of origin of the extracted plants [79], the extraction procedure [80][81][82], and the phenotype and genotypic differences of the strains tested [83]. De Sá Filho et al [79] recently reported that factors such as the physicochemical characteristics of soils, different dynamics of the action of climatic factors, and the consequent diversity of biological interactions in biomes greatly affect the chemical composition of plants.…”
Section: Inhibition Zone (Iz)contrasting
confidence: 99%
“…The absence of antimicrobial activity of the ethanolic extract of C. citratus observed in this study is also in disagreement with several other studies that have also investigated the antibacterial effect of lemongrass [75][76][77][78]. This difference between the results of the present study and those observed in others could be explained by several factors, such as the geographical area of origin of the extracted plants [79], the extraction procedure [80][81][82], and the phenotype and genotypic differences of the strains tested [83]. De Sá Filho et al [79] recently reported that factors such as the physicochemical characteristics of soils, different dynamics of the action of climatic factors, and the consequent diversity of biological interactions in biomes greatly affect the chemical composition of plants.…”
Section: Inhibition Zone (Iz)contrasting
confidence: 99%
“…Various hydrophilic solvents based on 35-90% methanol or ethanol are used for extracting phenolic acids and flavonoids, apigenin and luteolin derivatives, from the Lamiaceae. The optimal alcohol: water ratio is determined experimentally depending on the extraction conditions and chemical structure of the extracted compounds [Chaves et al 2020, Picos-Solas et al 2021]. Similar to our study, 80% methanolic solution was found to be appropriate for extracting flavonoid glucosides and rosmarinic acid from Salvia verbenaca or Rabdosia rubescens [Kostić et al 2015, Meng et al 2019].…”
Section: Discussionsupporting
confidence: 67%
“…Approximately 100 mg of SALVITILAB ® , Fontana, Menosan ®, and ACEF samples and 200 mg of chopped fresh sage leaves were added to 0.5 mL of 96.6% ethanol [ 33 ]. The mixtures were vortexed for 2 min, allowed to stand at 4 °C for 4 h, and vortexed again for another 2 min.…”
Section: Methodsmentioning
confidence: 99%